SUTIKA PARICHARYA: AYURVEDIC REVIEW - Chodankar Smita Sachin; Shinde Abhinav (International Journal of Applied Ayurved Research, 2020)
Sutika post natal is the most crucial period of woman’s life. All energy utilized for development, growth and giving birth to baby is regained and empowering her to face the further challenges of her life. This is the only period, if we not given attention lady may never get her energy back, & so Ayurvedic texts has given separate & special paricharya for this period. Aahara , Vihara, & emotional supplements described by aacharyas gives strength & support her for all her existence. In modern science only medicines & exercises are the only regimen for peapura but studding Ayurvedic paricharya Acharyas given attention towards all doshas, dhatus, malas including mana.